The Influence Of Products, Promotions, Prices, and Locations On Customer Satisfaction At Bank Bjb Batam City - Rumengan, Tommy Arby; Kurniati, Nia (Universitas Batam, 2021)
Bank BJB is one of the Regional Banks of West Java and Banten which has now turned into a bank on a national scale which has expanded to several regions in Indonesia such as North Sumatra, South Sumatra, Pekanbaru, and one of them is the Riau Islands, precisely in Batam City. With the aim of being able to provide service, renewal, introduction to customers outside Java, and create customer satisfaction in transactions. The purpose of this study was to determine the effect of product, promotion, price and location on customer satisfaction at Bank BJB Batam. The research method used is quantitative method, with the type of survey research where information is collected from respondents using a questionnaire. The population in this study were all customers of Bank BJB Batam City based on customer data from 2018-2022 which was 20,791. The sample in the study used the Slovin formula with accidental sampling technique, so that the number of samples obtained was 75 respondents. The data analysis technique was carried out by multiple linear regression analysis with the help of SPSS statistical tools. The results of the study found that the product had a significant effect on customer satisfaction, promotion had a significant effect on customer satisfaction, price had a significant effect on customer satisfaction, location had a significant effect on customer satisfaction, and simultaneously product, promotion, price, and location had a significant effect on customer satisfaction. The adjusted R Square value is 0.736 which can be called the coefficient of determination which in this case means 73.6% customer satisfaction can be obtained and explained by product, promotion, price and location. While the remaining 100% - 73.6% = 26.4% is explained by other factors, such as service quality, experiential marketing and others.